PERBANDINGAN ALGORITMA EFFICIENTNETB0 DAN INCEPTIONV3 DALAM KLASIFIKASI CITRA JENIS ANJING - Oriza Sativa Fiojati; Nani Mintarsih; Yuli Maharetta Arianti (Jurnal Ilmiah Teknik, 2023)
Dogs are pets that have hundreds of breeds. The various breeds of dogs can be distinguished by size, fur color, and type of fur. The identification of dog breeds can use images of dogs as one of the object recognition information. Image classification can be made using Deep Learning methods. Image classification is the process of grouping pixels in an image into a number of classes, so that each class can represent an entity with certain characteristics. Additionally, Deep Learning has many algorithms that can be used for image classification, including the InceptionV3 and EfficientNetB0 algorithms. The purpose of this research is to compare the accuracy results of the EfficientNetB0 and InceptionV3 algorithms in classifying dog breed images. The stages in making this program include collecting datasets, data preparation, model design, and interpreting the results. This image classification is made using the Python programming language and Visual Studio Code software. The program has an accuracy result with the best model being InceptionV3, with an accuracy of 97.30% on the training set and 97.07% on the validation set after 20 epochs.